THE EFFECT OF PRE-SOWING SEED TREATMENT WITH GROWTH SUBSTANCES AND SOWING DATES ON THE YIELD AND QUALITY OF MELON FRUITS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Under the conditions of newly irrigated light gray-earth soils of the Zarafshan Valley, the influence of pre-sowing seed treatment with growth substances and various sowing dates on the growth, development of plants, the formation of tops and roots, fruit elements, yield and quality of fruits of summer varieties of melon is studied. Technologies have been developed that provide a high and high-quality crop of summer varieties of melon Kuk kalla push, Obi Novvot Samarkand local and Kukcha-588.